2012
DOI: 10.4306/pi.2012.9.4.400
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Neuronal Cell Adhesion Molecule (NrCAM) Gene Variants with Personality Traits and Addictive Symptoms in Methamphetamine Use Disorder

Abstract: Objective1) To investigate the relationship between NrCAM polymorphisms and methamphetamine abuse in an ethnically homogenous Korean population. 2) To further support our findings by investigating the association among NrCAM gene variants, certain personality traits, and addictive symptoms of methamphetamine abusers.MethodsThirty-seven male methamphetamine abusers (age=43.3±7.8) and30 non-users (16 men, 14 women; age=59.8±10.4) were recruited. Ten single nucleotide polymorphisms (SNPs) in the NrCAM gene were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The SCN8A gene in humans is associated with cognitive impairment with and without cerebellar ataxia, and early infantile epileptic encephalopathy, and in mice it causes the motor endplate degeneration ( med ) phenotype (Burgess et al, 1995; Trudeau et al, 2006; Veeramah et al, 2012; O’Brien and Meisler, 2013). Nrcam mutations are associated with neurodevelopmental disorders and addictive behaviors in humans (Bonora et al, 2005; Sakurai et al, 2006; Ishiguro et al, 2006; Kim et al, 2009; Marui et al, 2009; Yoo et al, 2012). However, our point is not to make a direct case for NRCAM or SCN8A as human disease modifiers for CMT (indeed, their clinical associations are more severe than the “subclinical” mouse mutations we are describing) but instead to use them as a demonstration of the principle that variants that impact nodes will lead to more severe CMT phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The SCN8A gene in humans is associated with cognitive impairment with and without cerebellar ataxia, and early infantile epileptic encephalopathy, and in mice it causes the motor endplate degeneration ( med ) phenotype (Burgess et al, 1995; Trudeau et al, 2006; Veeramah et al, 2012; O’Brien and Meisler, 2013). Nrcam mutations are associated with neurodevelopmental disorders and addictive behaviors in humans (Bonora et al, 2005; Sakurai et al, 2006; Ishiguro et al, 2006; Kim et al, 2009; Marui et al, 2009; Yoo et al, 2012). However, our point is not to make a direct case for NRCAM or SCN8A as human disease modifiers for CMT (indeed, their clinical associations are more severe than the “subclinical” mouse mutations we are describing) but instead to use them as a demonstration of the principle that variants that impact nodes will lead to more severe CMT phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, over the last few years, a number of studies have reported that schizophrenia and bipolar disorder, as well as other psychiatric disorders, were associated with CAM, which is responsible for synapse formation and normal cell transmission (Corvin ; O'dushlaine et al ). Besides, neuronal CAM has been associated with drug abuse and personality characteristics such as novelty seeking and reward dependence (Yoo et al ). Additionally, the contribution of potassium channels, which were enriched gene sets for Extraversion in this study, has been reported in psychiatric disorders (Judy & Zandi ; Zhang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal CAM has been associated with drug abuse and personality characteristics such as novelty seeking and reward dependence. 48 Focal adhesion pathways are responsible for cell motility, proliferation, differentiation, survival and regulation of gene expression, 49 and have a major role in central nervous system development. The mitogen-activated protein kinase signaling pathway significantly associated with GC1 and GC2 is involved in cellular proliferation, differentiation and migration.…”
Section: Discussionmentioning
confidence: 99%